2020
DOI: 10.15566/cjgh.v7i5.479
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing social media technology during the COVID-19 pandemic to assist highly vulnerable populations in the Philippines

Abstract: National lockdowns and social distancing measures enforced in response to COVID-19 have forced many non-governmental organizations (NGOs) serving in low- and middle-income countries (LMICs) to suspend their operations. While low-income families continue to suffer from hunger and poverty, community quarantine restrictions additionally isolated them from town centers where healthcare, education, food, supplies, and livelihood opportunities are usually accessed. International Care Ministries (ICM) is a Philippine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Food distribution and marketing can be made more efficient by improving digital connectivity in Malaysia, especially in rural areas. A study by Go et al (2020) and the survey result of this paper has proved that Internet technology and social media platforms can be used as effective methods for responding to a range of disaster and crisis situations like the COVID-19 global pandemic. With better connection and good implementation of the Internet of Things (IoT), food security issues in the future can be mitigated more effectively.…”
Section: Conclusion and Recommendationsmentioning
confidence: 78%
See 3 more Smart Citations
“…Food distribution and marketing can be made more efficient by improving digital connectivity in Malaysia, especially in rural areas. A study by Go et al (2020) and the survey result of this paper has proved that Internet technology and social media platforms can be used as effective methods for responding to a range of disaster and crisis situations like the COVID-19 global pandemic. With better connection and good implementation of the Internet of Things (IoT), food security issues in the future can be mitigated more effectively.…”
Section: Conclusion and Recommendationsmentioning
confidence: 78%
“…4.1.3 Discussion paper 3: Utilizing social media technology during the COVID-19 pandemic to assist highly vulnerable populations in the Philippines Go et al (2020) found that Internet technology and social media platforms can be used as effective methods for responding to a range of disaster and crisis situations like the COVID-19 global pandemic. Access to healthcare, education, food, supplies, and livelihood affected the extreme low-income families through quarantine restrictions far from town centers.…”
Section: Discussion Paper 2: Utilization Of Data Mining Techniquesmentioning
confidence: 99%
See 2 more Smart Citations